Construction of hierarchical porous carbon nanosheets from template-assisted assembly of coal-based graphene quantum dots for high performance supercapacitor electrodes. (December 2017) - Zhang, Su; Zhu, Jiayao; Qing, Yan; Fan, Chengwei; Wang, Luxiang; Huang, Yudai; Sheng, Rui; Guo, Yong; Wang, Tao; Pan, Yanliang; Lv, Yan; Song, Huaihe; et al.
Abstract: Using coal-based graphene quantum dots (GQDs) as the building blocks, we develop a simple template-assisted assembly strategy to prepare hierarchical porous carbon nanosheets (HPCNs) for supercapacitor electrodes. The coal-based GQDs are prepared by a simple liquid phase oxidation of the bituminous coal. Benefiting from their small size, enriched edge structure, abundant functional groups, and good flexibility and chemical reactivity, these GQDs are suitable to construct complex nanoarchitectures for advanced energy storage materials. As a result, the HPCNs show an interconnected loose-stacking graphene-like structure with the specific surface area of 1332 m 2  g −1, hierarchical pore distribution, excellent conductivity, abundant active sites, and sufficient ion migration channels. An in situ chemical activation is further applied to improve its energy storage performance. Under the optimized conditions, the activated HPCN with a specific surface area of 1450 m 2  g −1 shows a greatly improved capacitive performance, with a high specific capacitance of 230 F g −1 (1 A g −1 ) and capacitance retention of 74% at 100 A g −1 (170 F g −1 ). No obvious capacity fade was found even after cycled at 10 A g −1 for 10, 000 times, demonstrating their excellent endurability. Our work may provide new thought for the effective use of abundant coal resource to design and preparation advanced carbon nanoarchitectures for energy storage. Graphical abstract: Highlights: A series of hierarchical porous carbon nanosheets (HPCNs) are prepared by a template strategy using coal-based graphene quantum dots (GQDs) as the building blocks. The unique interconnected loose-stacking graphene-like structure of the HPCNs endows their high specific surface area, hierarchical pore distribution, excellent conductivity, abundant surface active sites, and sufficient ion migration channels. Under the optimized conditions, the HPCN shows a high specific capacitance of 230 F g −1 and at the current density of 1 A g −1 with the capacity retention of 170 F g −1 at 100 A g −1 as well as excellent endurability.